Mother-to-Infant Bonding in Women With a Bipolar Spectrum Disorder - Boekhorst, Myrthe G. B. M.; Beerthuizen, Annemerle; Hillegers, Manon; Pop, Victor J. M.; Bergink, Veerle (Frontiers in Pediatrics, 2021)
Purpose Offspring of mothers with a bipolar disorder are at high-risk for impaired developmental outcomes and psychopathology (e.g. mood, anxiety, sleep disorders) later in life. This increased risk of psychopathology is not only because of genetic vulnerability, but environmental factors may play an important role as well. The often long and debilitating mood episodes of mothers with bipolar disorder might hamper their qualities as a caregiver and may impact the child. We examined early mother-to-infant bonding one year postpartum in mothers with bipolar spectrum disorder as compared to mothers of the general population. The association between mother-to-infant bonding and the type of bipolar spectrum diagnosis (bipolar I, bipolar II, bipolar Not Otherwise Specified) as well as relapse within 12 months postpartum was also assessed. Methods In total, 75 pregnant women with a bipolar spectrum disorder participated in the current study. The participants were included in a longitudinal cohort study of women with bipolar spectrum disorder and were prospectively followed from pregnancy until one year postpartum. Mother-to-infant bonding was assessed using the Pre- and Postnatal Bonding Scale. A longitudinal population-based cohort of 1419 pregnant women served as the control group. Multiple linear regression analyses were used to assess the association between bipolar spectrum disorder and mother-to-infant bonding scores, controlling for several confounders. Results Women with bipolar spectrum disorder perceived the bonding with their child as less positive compared to the control group. The type of bipolar spectrum disorder was not associated with poorer bonding scores. Relapse during the first year after delivery also did not affect bonding scores in women with bipolar spectrum disorder. Conclusions Our findings could imply that women with bipolar spectrum disorder are more vulnerable to impairments in bonding due to the nature of their psychopathology, regardless of the occurrence of postpartum relapse. Careful follow-up including monitoring of mother-to-infant bonding of pregnant women with a history of bipolar spectrum disorder should be a standard to this vulnerable group of women. In addition, regardless of severity and mood episode relapse, an intervention to improve bonding could be beneficial for all mothers with bipolar spectrum disorder and their newborns.